Exploring Relationship between Intrinsic Rewards, Extrinsic Rewards, and Employee Performance in University Academics - Muhammad Ahmad Mazher (East Asian Journal of Multidisciplinary Research, 2022)
This study investigates the relationship between employee performance at private universities in Lahore, Pakistan, and the extrinsic and intrinsic benefits that their employers provide them with. The empirical findings confirm that both intrinsic and extrinsic rewards have a positive and significant impact on employee performance for academic staff in private universities located in Lahore, Pakistan. The method of primary data study that we use allows us to collect the data using a questionnaire in a variety of private universities. Based on what we found, we think that it would be good for universities to offer incentives to their academic staff. These incentives could be either intrinsic or extrinsic, or they could be both.